Methodology, History, Pedagogical Methodology of Fine Arts (Texas Journal of Philology, Culture and History, 2023)
In this article, the history of modern directions of fine art and the methodology of contemporary depiction. In creative works of pedagogic artists, the ways of using different technologists were considered as an example of the principles of depicting a person in pencil drawing and painting composition in continuous education